2012
DOI: 10.1093/carcin/bgs249
|View full text |Cite
|
Sign up to set email alerts
|

The TNF-α/ROS/HIF-1-induced Upregulation of FoxMI Expression Promotes HCC Proliferation and Resistance to Apoptosis

Abstract: The proliferation-specific transcription factor Forkhead box M1 (FoxM1) acts as a master regulator of cancer cell growth and survival and plays an important role in the development of hepatocellular carcinoma. However, the molecular mechanisms that regulate FoxM1 expression remain largely unknown. In the current study, we demonstrated that tumor necrosis factor (TNF)-αα induced FoxM1 expression and transactivated its promoter activity in hepatoma cells. Serial 5" deletion and site-directed mutagenesis revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 44 publications
2
83
0
Order By: Relevance
“…In addition, ELK3 is known as a regulator of HIF-1α expression by modulating HIF-1α stability (21)(22)(23)30,31). HIF-1α plays a key role in the induction of cancer invasion, metastasis and angiogenesis, as well as in cancer growth, glucose metabolism, and other metastasis-associated signaling pathways (32)(33)(34)(35)(36). notably, HIF-1α is a key regulator of cancer metastasis and invasion in HCC (35,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ELK3 is known as a regulator of HIF-1α expression by modulating HIF-1α stability (21)(22)(23)30,31). HIF-1α plays a key role in the induction of cancer invasion, metastasis and angiogenesis, as well as in cancer growth, glucose metabolism, and other metastasis-associated signaling pathways (32)(33)(34)(35)(36). notably, HIF-1α is a key regulator of cancer metastasis and invasion in HCC (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α is a transcription factor that plays a well-established role in cancer development, progression and metastasis. HIF-1α is associated with the regulation of genes associated with cancer metastasis, invasion, angiogenesis, cellular proliferation, apoptosis and glucose metabolism (32)(33)(34)(35)(36). Vascular endothelial growth factor (VEgF) and metalloproteinase-2 (MMP-2), which are target molecules of HIF-1α, are also linked to the development, invasion and metastasis of HCC (35)(36)(37)(38).…”
Section: Elk3 Promotes the Migration And Invasion Of Liver Cancer Stementioning
confidence: 99%
“…Conversely, experiments in macrophages from Foxm1 -/-mice and FOXM1-deficient primary amnion cells showed increased levels of IL-6 (Lim et al, 2014;Balli et al, 2012). Another adipokine TNF-a decreases the expression of FOXO3 at the transcript level (Sente et al, 2016) and increases FOXM1 expression to promote cell proliferation and the resistance to apoptosis (Xia et al, 2012) (Fig. 3 B).…”
Section: Acdh-11mentioning
confidence: 95%
“…TNF-a has pleiotropic functions in inflammatory progression depending on cell type or biological context 7 . In certain conditions, TNF-a induces apoptosis; however, recent studies have indicated that TNF-a may promote hepatocellular carcinogenesis by activating a variety of signal pathways related to cell proliferation, differentiation and survival [8][9][10] . The mechanism of inflammation linked to TNF-a and involved in hepatocellular carcinogenesis still needs to be fully elucidated.…”
mentioning
confidence: 99%